Effect of comprehensive vasodilation vs usual care on mortality and heart failure rehospitalization in women with acute heart failure. (25th November 2020) - Wussler, D; Walter, J; Kozhuharov, N; Goudev, A; Flores, D; Maeder, M; Shrestha, S; Gualandro, D; De Oliveira, M.T; Kobza, R; Rickli, H; Breidthardt, T; et al.
Abstract: Background: Guidelines recommend evaluating the risk/benefit ratio of novel therapies individually in women and men, as the pathophysiology and the response to treatment may differ between women and men. Among patients with acute heart failure (AHF), a strategy of intensive vasodilation, compared with usual care, overall did provide comparable outcomes. Purpose: To evaluate the effect of a strategy that emphasized early intensive and sustained vasodilation in women with AHF. Methods: In a randomized, open-label blinded-end-point trial patients hospitalized for AHF were enrolled in 10 hospitals in Switzerland, Bulgaria, Germany, Brazil, and Spain. Inclusion criteria were AHF expressed by acute dyspnea and increased plasma concentrations of natriuretic peptides, systolic blood pressure ≥100mmHg, and a plan for treatment in a general ward. Patients were randomized 1:1 to a strategy of early intensive and sustained vasodilation throughout the hospitalization or usual care. The primary end point was a composite of all-cause mortality or rehospitalization for AHF at 180 days. Results: Among 788 patients randomized, 781 completed the trial and were eligible for the primary end point analysis. Of these 288 (36.9%) were women. The primary end point, a composite of all-cause mortality or rehospitalization for AHF at 180 days, occurred in 53 female patients (37.9%) in the intervention group (including 28 deaths [20.0%]) and in 34 female patients (23.0%) in the usual care group (including 22 deaths [14.9%]) (absolute difference for the primary end point, 14.9%; adjusted hazard ratio, 1.67 [95% CI: 1.08–2.59]; P=0.02). Clinically significant adverse events with early intensive and sustained vasodilation vs usual care included hypotension (8% vs 2%). Conclusion: Among women with AHF, a strategy of early intensive and sustained vasodilation, compared with usual care, had a detrimental effect on a composite outcome of all-cause mortality and AHF rehospitalization at 180 days. Funding Acknowledgement: Type of funding source: None